2016
DOI: 10.1089/jir.2016.0035
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium cutisLysate Treatment Can Increase the Efficacies of PPR Vaccine

Abstract: This study aimed to evaluate the effects of Peste des petits ruminants (PPR) vaccine on cytokine and antibody levels in sheep when administered alone or in combination with Corynebacterium cutis lysate (CCL). The PPR vaccine group received a single subcutaneous axillary injection of the PPR vaccine (1 mL containing tissue culture infectious dose (TCID) attenuated live PPRV, n = 6) and the combination treatment (1 mL CCL and 1 mL PPR vaccine, n = 6) groups received a single subcutaneous axillary injection of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Er et al (2015 ) found that CCL administration did not cause a significant change in hematological parameters in sheep. Dik et al (2016) determined that the administration of CCL showed a decrease in the numbers of WBC and LYM in sheep. This study is accordance with the study conducted by Er et al (2015) by similarly concluding that there was no statistically significant difference when animals within the Group E based on days were compared, the comparison of the Group E with the Group F was performed and the overall comparison of group-based general evaluations of hematological parameters was taken into consideration (P>0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Er et al (2015 ) found that CCL administration did not cause a significant change in hematological parameters in sheep. Dik et al (2016) determined that the administration of CCL showed a decrease in the numbers of WBC and LYM in sheep. This study is accordance with the study conducted by Er et al (2015) by similarly concluding that there was no statistically significant difference when animals within the Group E based on days were compared, the comparison of the Group E with the Group F was performed and the overall comparison of group-based general evaluations of hematological parameters was taken into consideration (P>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This study is accordance with the study conducted by Er et al (2015) by similarly concluding that there was no statistically significant difference when animals within the Group E based on days were compared, the comparison of the Group E with the Group F was performed and the overall comparison of group-based general evaluations of hematological parameters was taken into consideration (P>0.05). Yılmaz et al (2011) argued that the use of CCL led to an increase in the level of IgG in the colostrum and serum of sheep and in newborns, Dik et al (2016) pointed out that the protective immune response continued throughout the study process in sheep which received combined treatment (CCL and PPR vaccine) although the peak level of Abs in the group started 7 days after administration, In addition, Saat et al (2016) stated that the IgG ratio in the milk of cattle with mastitis increased significantly after the admin-5580 Ö. AYDIN, M.S. AKTAŞ istration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The undesirable effects of drugs or diseases in organs or systems can be determined by biochemical and hematological parameters [ 1 , 13 ]. Free oxygen radicals produce by various agents such as LPS cause oxidative stress and cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…Free oxygen radicals produce by various agents such as LPS cause oxidative stress and cellular damage. Thiobarbituric acid reactive substances (TBARS) are detected in the cellular damage [ 13 , 47 ]. The underlying cause of oxidative stress in endotoxemia is cell damage and excessive TNF-α levels [ 38 ].…”
Section: Introductionmentioning
confidence: 99%